Path towards an attainable quality : the effect of tooling design on the product competency and process efficiency - Tamilarasi, Arasu (2023)
People gradually started to rely on electronic devices such as computers, smartphones, and so on as their lives became increasingly dependent on them. These products are made up ofseveral Integrated Circuits (IC) which are connected among themselves with copper traces and undergo numerous processes before becoming a finished product. Due to its importance, it is vital to produce printed circuit board assemblies that are high in quality and low in the probability of malfunctioning. Therefore, certain issues need to be carefully resolved to ensure the reliability of the products. In addition, several problems have been identified during this study. A large yield drop and high rejects have been observed at specific stations where operators perform mechanical assembly of printed circuit boards. In addition, the lack of a clear understanding of the process of the operators has led to defects at the station. Aside from that, operators manually assemble the mechanical part using poorly designed tooling that is not designed for printed circuit board assembly. Since it is highly error-prone due to human error, this technique is known to have a high rejection rate. As a result of high rejects and unfit tooling used, the cycle time of producing the product has been increasing abruptly. To produce defect-free products, this study will explore a technical method to explore defect occurrences and classify their root causes by using existing quality tools, such as defect cycle analysis and fault tree analysis (FTA). Additionally, this study examines the possibilities of designing tooling using more structured guidelines such as "Verein Deutscher !ngenieure 2221" (VDT 2221), which makes the process simpler and allows for the evaluation of each task taken in designing and its significant impact. Eventually, the processing time of the products is brought down to optimal, which maximizes productivity and increases customer satisfaction. The data for this study were collected through various channels such as system data, observations, semi-structured interviews among the operators, discussion and brainstorming, and finally real-time experiments and trials. In sum, this study helped eliminate all defects related to mechanical assembly, which resulted in a reduction of overall defects by 81.3%, a reduction of scrap by 57% (total saving ofUSD 5920), and a reduction of the cycle time by 28.57% (saving of USD 419 in two quarters). Based on these results, it is crucial to identify the correct method of defect detection, the point ofoccurrence, and the root cause ofthe defect. Through this study, a well-organized generic method of designing tooling has been developed as well. Nonetheless, this study hopes to offer a few techniques that are being practiced to increase quality with a lesser time used.